Occupational health disparities improving the well-being of ethnic and racial minority workers - Leong, Frederick 1957-; Eggerth, Donald E.; Chang, Chu-Hsiang; Flynn, Michael A.; Ford, J. Kevin ca. 20./21. Jh; Martinez, Ruben Orlando 1952- (American Psychological Association, 2017)
"According to a recent report from the World Health Organization (WHO) Commission on the Social Determinants of Health, "a girl born in Sweden will live 43 years longer than a girl born in Sierra Leone." The report goes on to observe that "in Glasgow, an unskilled, working-class person will have a lifespan 28 years shorter than a businessman in the top income bracket in Scotland" (see Footnote 1, p. 5). Commenting on these sobering statistics of health disparities around the world in an invited address, Vicente Navarro (2009) of Johns Hopkins University noted that: the mortality differentials among countries are enormous. But such inequalities also appear within each country, including the so-called rich or developed countries. ... We could add here similar data from the United States. In East Baltimore (where my university, the Johns Hopkins University, is located), a black unemployed youth has a lifespan 32 years shorter than a white corporate lawyer.
Includes bibliographical references and index
Keywords: Arbeitsmedizin; Industrial hygiene / Moral and ethical aspects; Minorities / Employment; Minorities / Health and hygiene; Occupational Health / ethics; Minority Groups; Minority Health; Aufsatzsammlung